PENGARUH TERAPI BACK MASSAGE TERHADAP PENURUNAN NYERI RHEUMATOID ARTHRITIS PADA LANSIA - RIZKA MAILANI PUTRI; AMIR LUTFI; ALINI ALINI (Jurnal Ners, 2020)
Elderly is someone who has reached the age of 60 years and over. As you get older, your physiological function decreases, which causes various health problems, one of which is Rheumatoid Arthritis. Rheumatoid Arthritis is characterized by pain. One way to treat pain is back massage therapy, because back massage therapy can provide a sensation of relaxation, resulting in vasodilation of the blood vessels in the area being rubbed so that cell activity increases and will reduce pain and support the healing process. The purpose of this study was to determine the effect of back massage therapy on the reduction of Rheumatoid Arthritis pain in the elderly in the working area of the Kampar Public Health Center in 2020. The design of this study was quasi experimental with a one group pretest-posttest design. The population in this study was 570 people with a sample size of 30 people. The sampling method was purposive sampling. The measuring instrument used is the numeric rating scale and the observation sheet. The analysis used was univariate and bivariate using the non-parametric Wilcoxon Signed Rank Test. The results showed the effect of back massage therapy on the reduction of Rheumatoid Arthritis pain in the elderly with a p-value of 0.000 (p